Synchronous Buck Converter with Perturb and Observe Maximum Power Point Tracking Implemented on a Low-Cost Arduino-microcontroller (Journal of Engineering, 2018)
Maximum power point tracking (MPPT) is used in photovoltaic (PV) systems to enhance efficiency and maximize the output power of PV module, regardless the variation of temperature, irradiation, and the electrical characteristics of the load. A new MPPT system has been presented in this research, consisting of a synchronous DC-DC step-down Buck converter controlled by an Arduino microcontroller based unit. The MPPT process with Perturb and Observe method is performed with a DC-DC converter circuit to overcome the problem of voltage mismatch between the PV modules and the loads. The proposing system has high efficiency, lower cost and can be easily modified to handle more energy sources. The test results indicate that the use of the proposed MPPT control with the designed synchronous Buck converter increases the PV output power; hence increases the overall solar system efficiency. The synchronous Buck converter test results used in this design showed high converter efficiency up to 95% of the power produced from the solar module, leading to reduce power loss caused by the power transfer process from PV module to the loads.